Analisis Implementasi Manajemen Pengabdian Masyarakat dan Penelitian Dosen dalam Upaya Peningkatan Peringkat Universitas: Studi Kualitatif Deskriptif pada Universitas Pamulang dan Universitas Budi Luhur di Jabodetabek - Juwita Ramadani Fitria; Sri Sri Handayani; Nana Herdiana Abdurahman; Supatmin Supatmin; Yohanes Aris Sri Sadono; Sri Mulyani (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This study aims to analyze the implementation of community service management (PKM) and lecturer research in an effort to improve the ranking of private universities, with case studies at Pamulang University and Budi Luhur University in the Greater Jakarta area. Using a descriptive qualitative approach, this study involved in-depth interviews with 20 lecturers, participatory observation, documentation studies, and focus group discussions (FGD). Data analysis was carried out with a thematic approach that resulted in four main themes: (1) PKM and Research Management Policies and Strategies, (2) Implementation of PKM Management and Research, (3) Obstacles and Challenges, and (4) Impact on University Rankings. The results show that both universities have developed comprehensive policies and strategies in PKM management and research, but with different approaches. Pamulang University applies a decentralized management approach with an integrated information system, while Budi Luhur University applies a centralized approach with a focus on external partner collaboration. The main obstacles faced include the high workload of lecturers, limited access to research resources, and challenges in building a research culture. Effective PKM management and research have been shown to correlate positively with improved university rankings, especially through increased scientific publications and citations. These findings have implications for the importance of comprehensive policy development, information technology integration, strengthening external collaboration, and constraint mitigation strategies in PKM management and research to improve the ranking of private universities in Indonesia.